Risk prioritization methodology for decision makers - Macedo de Lima, Igor; Cristina de M. de Lima, Paula; Cassiano de Góes Filho, Gilson; Cesar de Faria Nogueira, Edison; Cristina Ramos Faustino, Bruna (Seven Editora, 2023)
Changes in regulatory standards, especially NR-01 with the obligation to prepare a Risk Management Program (RMP) has increased pressure on organizations to manage occupational risks. Companies need to establish mechanisms to protect the health and safety of their employees to meet legal obligations and reduce the damage caused to their employees and society. Organizations need to recognize the risks that make up their activities and establish measures to eliminate or reduce the potential damage that these risks can cause , and the proposed methodology seeks to solve this problem. DOI: 10.56238/pacfdnsv1-029